2021
DOI: 10.1111/ddi.13242
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of black grouse trends in the French Alps: The prevailing contribution of climate

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…The sensitivity of chicks in black grouse and other tetronids to weather has been reported repeatedly (Hissa et al 1983, Zbinden and Salvioni 2004,Baines et al 2007). Although the weather is usually synchronized over large spatial areas, the complicated mountainous surface can result in effects that differ at small spatial scales and hence in only weak population synchrony (Cattadori et al 2000, Canonne et al 2021). This differs from black grouse populations from Scandinavia that may cycle and exhibit large‐scale synchrony (Lindström et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of chicks in black grouse and other tetronids to weather has been reported repeatedly (Hissa et al 1983, Zbinden and Salvioni 2004,Baines et al 2007). Although the weather is usually synchronized over large spatial areas, the complicated mountainous surface can result in effects that differ at small spatial scales and hence in only weak population synchrony (Cattadori et al 2000, Canonne et al 2021). This differs from black grouse populations from Scandinavia that may cycle and exhibit large‐scale synchrony (Lindström et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Black grouse population dynamics are typically characterized by strong temporal variation of breeding success (Moss 1986, Zbinden and Salvioni 2004) and by large‐scale population synchrony in some areas (Lindström et al 1996, Baines et al 2007), but not in others (Cattadori et al 2000, Canonne et al 2021). Detailed radio‐tracking studies have provided insights into different components of productivity (Marjakangas and Törmälä 1997, Caizergues and Ellison 2000, Warren and Baines 2002, Bowker et al 2007) and in the survival of both adults and juveniles (Angelstam 1984, Willebrand 1992, Caizergues and Ellison 1997, Baines et al 2007, Bowker et al 2007, Pekkola et al 2014).…”
mentioning
confidence: 99%
“…We extracted snowmelt dates from the Moderate Resolution Imaging Spectroradiometer (MODIS), defining the date of snowmelt as the end of the period of continuous snow cover. Date_100 corresponded to total snowmelt at the counting sites (100% of pixels of the site with bare ground), and Date_50 to 50% bare ground (Canonne et al, 2021; Novoa et al, 2016). Covariates built from SAFRAN and MODIS data were calculated for the Dévoluy area (Appendix S1) for the survival analysis (as all birds were caught in this area), and on the summer counting sites for the analysis of fecundity.…”
Section: Methodsmentioning
confidence: 99%
“…We expected a long vegetative season to positively influence birds' body condition and overall survival, given the longer period to accumulate resources and frequent attempts of double brooding (Bernard‐Laurent et al, 2017). Many studies have shown the importance of snowmelt timing on the development of vegetation phenology and the nutritive value of food resources for reproductive hens as well as for chicks (Canonne et al, 2021; Novoa et al, 2016). Breeding period temperatures and precipitations hypothesis …”
Section: Introductionmentioning
confidence: 99%
“…Hunting is generally not considered a threat in countries with relatively dense and contiguous black grouse populations such as Russia and Scandinavia, where it is a popular game species. Instead, the main drivers of black grouse population declines are believed to be non‐human predation (Jahren et al, 2016) and anthropogenic activities leading to habitat loss, fragmentation and degradation (Storch, 2000, 2007; Storch & Segelbacher, 2000; Ten Den & Niewold, 2000), including forestry and agricultural activities (Klaus, 1991; Ludwig et al, 2008), tourism (Tost et al, 2020) and climate change (Canonne et al, 2021; Ludwig et al, 2006). Nevertheless, black grouse may be vulnerable to hunting because reproduction takes place on temporally and spatially predictable leks (Höglund & Alatalo, 1995; Lampila et al, 2011; Zbinden et al, 2018).…”
Section: Introductionmentioning
confidence: 99%